Method of detection of external contours of aircraft wing - Казак, В.М.; Гальченко, С.М.; Бикус, Л.В.; Бугрій, К.М. (Proceedings of National Aviation University (archive), 2006)
Examining problem of indicated external surface wing of the plain in a flight with the object of the moment determination the place and power of arising damage.